Abundance, Composition and Distribution of Phytoplanktonin Calamianes, Palawan - Asis, Jules Jason C; Campos, Wilfredo L; Nabuab, Fenelyn M (Science Diliman: A Journal of Pure and Applied Sciences, 2007)
Phytoplankton in Coron Bay of the Calamianes Islands, Palawan were investigated from 27-29 May2004. Samples were collected from 33 stations by filtering five 10 L buckets of surface water through a net with a 20 µm mesh bag. The phytoplankton consisted of four major groups. Diatoms, showed the highest mean density of 1432.9 ind•L -1 . Silicoflagellates comprised the next most abundant group with a mean density of 132.3 ind•L -1 . Dinoflagellates followed with a mean density of 94.8 ind•L -1 , while the cyanobacteria (blue-green algae) had a mean density of 19.4 ind•L -1 . The top three diatoms were Chaetoceros , Bacteriastrum and Coscinodiscus . The genus Peridinium was the most abundant dinoflagellate, while Tintinnopsis dominated the silicoflagellates. Among the cyanophytes, Trichodesmium showed the highest density. High phytoplankton concentrations were observed in the vicinity of a pearl farm and in areas adjacent to mangrove forests. Overall abundance and diversity in the study area are higher than in other similarly reef-dominated areas in the country. This may be attributed to factors on both large and local scales.